The Effect of Herbal Therapy on Emesis Gravidarum - Assa Aprin Tania; Ika Yudianti; Eny Sendra; Ririn Indriani (Indonesian Journal of Sport Management and Physical Education, 2022)
Handling emesis gravidarum using conventional drugs has a teratogenic risk, so another effort is to provide subscriptions using herbal therapy. This study was conducted to determine the effect of herbal therapy in reducing the frequency of emesis gravidarum Method: This type of research is a literature review using the Pubmed, Research Gate, SINTA database. Literature collection strategy using the PICO framework was then analyzed until there were 16 literature that could be used. The review method used is to compare and contrast to find similarities in the types of herbal therapy and the dissimilarities of the most effective herbs. There are differences in the frequency of emesis gravidarum in the use of ginger, mint, lemon, quince, lavender, orange herbs which are provided in the form of extracts and aromatherapy. Giving herbal therapy in the form of ginger, mint, lemon, quince, lavender, orange with aromatherapy and extract preparations can reduce the frequency of emesis gravidarum.